Clinanthus microstephium, an Amaryllidaceae species with Cholinesterase Inhibitor Alkaloids: Structure−Activity analysis of Haemanthamine skeleton derivatives - Adessi Cofré, Tonino Graziano (2019)
Plants of the Amaryllidaceae family are well-known (not only) for their ornamental value but also for the alkaloids that they produce. In this report, the first phytochemical study of Clinanthus genus was carried out. The chemical composition of alkaloid fractions from Clinanthus microstephium was analyzed by GC/MS and NMR. Seven known compounds belonging to three structural types of Amaryllidaceae alkaloids were identified. An epimeric mixture of a haemanthamine-type compound (6-hydroxymaritidine) was tested as an inhibitor against acetyl- and butyrylcholinesterase enzymes (AChE and BChE, respectively), two enzymes relevant in the treatment of Alzheimer's disease, with good results. Structure–activity relationships through molecular docking studies with this alkaloid and other structurally related compounds were discussed.